STEM-Based Everyone is a Teacher Here Strategy on Metacognitive Abilities - Levina Syafaa Averina; Mayarni (Jurnal Ilmiah Sekolah Dasar, 2022)
The low quality of education have an effect quality of the nation. One of efforts to improve quality of education in Indonesia involve metacognitive abilities. The component of cognitive regulation in metacognitive will make the students mind systematic. This study aims to analyze the STEM-based learning strategy everyone is a teacher here on metacognitive abilities. The type of this research  was a quasi experimental design with a pre-test and post-test control group design. The amount of data sample of this research is 103 students of fifth grade and the research sample amount is 55 students. The research instrument used has been through validity and reliability tests. Data analysis used in this study were normality test (Kolmogorov-Smirnov) and hypothesis testing (Wilcoxon test and Mann Whitney test).The result showed an increase in metocnitive abilities outcome that can be seen based on the result of pre-test and post-test, experiment class and control class. It was proven in testing the hypothesis, which states that value Asymp. Sig (2-tailed) 0,047 < 0,05 which means Ho is accepted and Ha is rejected. So it can be conclude that learning using the STEM-based learning strategy of everyone is a teacher here is effective in incrase the metacognitive abilities of students. Through STEM-based learning strategy everyone is a teacher here, metacognitive abilities can be enhanced based on soft skill, hard skill and creativity in building knowledge in the science learning process throught the water cycle and impact on living beings.